2011
DOI: 10.1007/s00405-011-1587-x
|View full text |Cite
|
Sign up to set email alerts
|

Laser and topical mitomycin C for management of nasal synechia after FESS: a preliminary report

Abstract: The objective of the study is to assess the role of diode laser coupled with topical mitomycin C (MMC) in the management of synechia after endoscopic sinus surgery. Twenty-five patients with recurrent sinusitis due to synechia between the middle turbinate and lateral nasal wall after endoscopic sinus surgery were included in this study. Diode laser was used to divide the synechia and MMC was applied topically in the area of the middle meatus for 5 min. Patients were followed for 6 months to assess symptoms imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Attempts to limit such adhesion formation with anatomical barriers have met with limited success. 4 Animal studies in rabbits suggest that MMC slows the postoperative healing process of nasal mucosa, reduces stenosis without affecting re-epithelialization. Experimental studies observed the effects of brief exposure of MMC on cultured human nasal mucosa fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts to limit such adhesion formation with anatomical barriers have met with limited success. 4 Animal studies in rabbits suggest that MMC slows the postoperative healing process of nasal mucosa, reduces stenosis without affecting re-epithelialization. Experimental studies observed the effects of brief exposure of MMC on cultured human nasal mucosa fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mitomycin-C (MMC): MMC is an alkylating antineoplastic antibiotic that prevents replication of fibroblasts and epithelial cells, in otolaryngology MMC is currently under inquiry for the prevention of laryngotracheal stenosis, as an adjunct to FESS to prevent closure of the maxillary sinus antrostomy. 4 MMC operates by disrupting base paring of DNA molecules in the G-1 phase of cell cycle, and inhibits formation of RNA and protein synthesis-this way inhibits proliferation of fibroblasts. Additional function is inhibition of apoptosis in fibroblasts and blockage of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation